INFORMATION SECURITY: ANALYSIS OF THE MAIN THREATS TO UKRAINE - Korol’ , V.S. (The actual problems of regional economy development, 2019)
In modern conditions of the XXI century. information security is becoming more and more important, and the issue of its provision is becoming more acute. The rapid introduction of information technology in all spheres of society and development in the context of globalization processes, actualizes the problem of determining reasonable and effective ways of ensuring information security. The problem of information security of Ukraine and protection of the national information space from negative influences was investigated. The theoretical approaches to the definition of the essence of the notion of information security are analyzed; the types of real and potential informational threats for Ukraine are thoroughly investigated. The practical recommendations for improving the state information policy and creation of an effective information security system of Ukraine are defined.